Performance evaluation of a developed evaporative air cooler with solar irradiance effect - T.Mustafa, Ayad; S.Jasim, Hassan (International Journal of Engineering and Technology, 2019)
Direct evaporative air cooler has been developed to enhance the cooling effectiveness in hot and low relative humidity region. The evaporation area of the conventional evaporator was increased and tested in Baghdad city (N33.3, E44.4). The present study aims to evaluate the developed evaporative air cooler under the direct effect of the solar irradiance and dry-bulb temperatures variation. For test conditions with low relative humidity range 10 to 15 percent, it is found that inlet dry-bulb temperature of the air could be cooled lower than wet-bulb temperature. The cooling effectiveness tends to rise when inlet dry-bulb temperatures increase between 26.3Â°C to 44.7Â°C. Inversely, the cooling effectiveness tends to reduce when the solar irradiance affects between 268 W/m2 to 636 W/m2. Moreover, the cooling effectiveness of the developed evaporative air cooler in shade is higher than that in sunny places of Baghdad by 10%. The energy savings by using the developed evaporative air cooler are 80% and 84% in sunny and shade places, respectively, when compared to an identical vapor compression air conditioning unit. In conclusion, it was found that increasing the area of evaporation is an efficient method to increase cooling effectiveness, while solar irradiance has the opposite effect.Â Â